Perencanaan dan pelaksanaan supervisi akademik oleh pengawas pada guru Agama Kristen - Wolter Weol; Olivia Cherly Wuwung; Subaedah Luma (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The purpose of this study was to obtain a clear and detailed description of: Planning and implementation of academic supervision by PAK supervisors for Christian Religion teachers at SMP Negeri 5 Ranoyapo. Associated with obtaining information and a clear and systematic picture in using a qualitative approach where as a researcher tries to photograph, describe and interpret every phenomenon of the object under study in accordance with the objective situation and conditions. The results showed that planning for academic supervision by PAK supervisors for Christian religious teachers at SMP Negeri 5 Ranoyapo was generally carried out because it had become the main task, function and responsibility of the supervisor; based on the program from the ministry of religion which is embodied in the supervisory program and follows the academic calendar of the education unit; Implementation of academic supervision by PAK supervisors on Christian Religious Education teachers at SMP Negeri 5 Ranoyapo, in its implementation there are differences between sites: a) Site 1, held twice every semester; b) Site 2, held in each semester only once; 3) Site 3, practically it is not done at school, but during MGMP.